Study of Metacognition among Senior Secondary Students in relation to their Problem-Solving ability and Self-Esteem - Kaur, Navdeep; Rai, Monkia (Voices of Teachers and Teacher Educators, 2024)
The study’s major goal is to examine how students in secondary schools use metacognition in relation to their capacity for problem-solving and their sense of self. Metacognition is a specialized concept in psychology that refers to the understanding of one’s own cognitive processes. Metacognition helps to develop the Problem-Solving ability of a learner, which can be applied in solving the obstacles of life in an effective manner. Metacognition also bears a relationship with the self-esteem of a person. The present study was undertaken in the context of metacognition, problem-solving and self-esteem. Following a descriptive research design 200 secondary school students of Amritsar were chosen as sample through simple random sampling. The data was collected with the help of standardized tools prepared by Punita Govil (Meta Cognition Inventory), L.N. Dubey (Problem-Solving ability test) and G.P Thakur (Self-Esteem Inventory). The results of the study showed that while male and female students’ abilities to solve problems were comparable, female students’ metacognition skills were much higher. However, male students’ self-esteem was much higher than that of female students. It was also found out that metacognition does not have any impact on the Problem-Solving ability, however there is positive and negative impact of Metacognition on Self-Esteem